The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/membranes9080104
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Gas Transport Behavior in Cross-Linked Liquid Crystalline Polyacrylate Membranes

Abstract: Stable, cross-linked, liquid crystalline polymer (LCP) films for membrane separation applications have been fabricated from the mesogenic monomer 11-(4-cyanobiphenyl-4′-yloxy) undecyl methacrylate (CNBPh), non-mesogenic monomer 2-ethylhexyl acrylate (2-EHA), and cross-linker ethylene glycol dimethacrylate (EGDMA) using an in-situ free radical polymerization technique with UV initiation. The phase behavior of the LCP membranes was characterized using differential scanning calorimetry (DSC) and X-ray scattering,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…11 Based on our previous work, there is still some focus worth further study, such as temperature, which is an important factor that affects the microstructures and macroscopic properties, especially for some high-polarity materials. 14,15 Many studies have indicated that the effect of temperature on cavity size, 16 hysteresis, 17 conductivity, 18,19 dielectric properties, 20 straininduced crystallization 21,22 and mechanical properties 23,24 of rubbers and their composites is nonnegligible. Many properties of materials containing a large number of hydrogen bonds show more obvious temperature dependence, which results from the high temperature sensitivity of hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…11 Based on our previous work, there is still some focus worth further study, such as temperature, which is an important factor that affects the microstructures and macroscopic properties, especially for some high-polarity materials. 14,15 Many studies have indicated that the effect of temperature on cavity size, 16 hysteresis, 17 conductivity, 18,19 dielectric properties, 20 straininduced crystallization 21,22 and mechanical properties 23,24 of rubbers and their composites is nonnegligible. Many properties of materials containing a large number of hydrogen bonds show more obvious temperature dependence, which results from the high temperature sensitivity of hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%